OWE-05 Interim long-term safety/efficacy of risankizumab treatment in crohn's disease patients from the open-label extension study. Issue 2 (June 2019) - Ferrante, M; Panes, J; Baert, F; Louis, E; Kaser, A; Gustafson, D; Hall, D; Böcher, WO; Herichova, I; Liao, X; Wallace, K; Kalabic, J; et al.
Abstract : Introduction: Adults with moderate-to-severe Crohn's disease (CD) who responded to risankizumab (RZB) in the phase 2 induction and maintenance study (Feagan, 2017) could enroll in an open-label extension (OLE) study. Interim efficacy and safety of RZB maintenance treatment from the OLE, up to 2 years, are reported. Methods: Patients (pts) achieving clinical response (decrease from baseline [BL] in CD Activity Index [CDAI] ≥100) without remission (CDAI <150) after wk 26 or clinical response and/or remission after wk 52 of the preceding study received 180 mg s.c. RZB every 8 wks for up to 216 weeks. Pts losing clinical response or remission after completing the preceding study were re-induced with 600 mg i.v. RZB at wk 0, 4, 8. Pts received subsequent 180 mg s.c. RZB maintenance treatment only if they achieved response or remission following re-induction treatment. Ileocolonoscopy was performed yearly. Efficacy data (clinical remission and endoscopic remission [CD Endoscopic Index of Severity (CDEIS) ≤4 or CDEIS ≤2 for pts with initial isolated ileitis]) are reported up to wk 48. Non-responder imputation (NRI) was used for missing data. Results: A total of 65 pts were enrolled (including 4 who were re-induced). Mean (standard deviation) exposure to RZB was 657.2 (190.73) days. At the data cut-off, 14 (21.5%) pts have discontinued the study. Up to wk 48, clinical remission rates were sustained and the proportion of pts with endoscopic remission increased from BL (table 1 ). Adverse events (AEs) were reported for 58 (89.2%) pts; 18(27.7%) pts had serious AEs. AEs occurring in >10% of pts were nasopharyngitis (26.2%), fatigue (16.9%), arthralgia and worsening CD (15.4% each). Four serious infections in 5 pts were perianal abscess (n=1), Campylobacter (n=1), viral gastroenteritis (n=2), and peritonitis (n=2). No events of tuberculosis, malignancies or deaths occurred. Conclusions: In this interim analysis, clinical remission and endoscopic remission were sustained in CD pts receiving long-term RZB treatment. The safety profile of RZB was consistent with previously published data (Feagan, 2017). References: Feagan BG, et al. Lancet 2017, 29;389(10080):1699–1709. Feagan BG, et al. Gastroenterology 2017;152(5):S1310.